Using Computer Programs to Improve Artistic and Performance Skills of 5-7th Grade Students - Marufjon Ashurov Abdumutalibovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
It is desirable to strengthen children's sense of dividing the musical period into stages, to move to music, to offer children to play musical instruments, to observe singing and pesas with music. The article describes the methods of using computer programs to improve artistic and performance skills of 5-7th grade students.